Analysis of Employee Discipline Implementation in the Regional Secretariat of North Central Timor District - Johanes Eudes Manuel Atolan Soares; Wiliam Djani; Lenny Magdalena Tamunu (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
AbstractIn connection with the work discipline of the state civil apparatus, the Government issued a regulation regarding employee discipline which contains obligations, prohibitions and sanctions for employees who violate. This regulation was made with the aim of improving the professionalism of civil servants, ensuring order, and the smooth execution of duties and accelerating decision making in the event of disciplinary violations of Civil Servants (PNS), as stipulated in Government Regulation Number 53 of 2010 concerning Civil Servant Discipline ( Civil servants). To improve discipline for the Civil Servants (PNS) of North Central Timor Regency, since 2013 the Regional Government has implemented the mandate set out in Government Regulation Number 53 of 2010. However, in its application there are still many employees who are not disciplined in their work. This research is intended to analyze and describe the implementation of Government Regulation No. 53/2010 concerning Civil Servant Discipline at the Regional Secretariat of Timor Tengah Utara Regency. This study uses descriptive qualitative methods and data analysis techniques Milles and Huberman. The results of the study show that the Civil Servants in the Regional Secretariat of North Central Timor Regency in terms of PNS discipline have not been optimal and the level of discipline of Civil Servants is still very low which is evidenced by the level of violations and the imposition of disciplinary sentences of Civil Servants year and the dominant types of violations were committed, namely moderate to serious violations. As for other problems, namely the lack of socialization related to PNS discipline at the Regional Secretariat of North Central Timor Regency based on Government Regulation number 53 of 2010, Lack of understanding of Civil Servants of existing regulations due to lack of interest in reading civil servants to applicable regulations, and lack of assertiveness and courage by the leadership. OPD in imposing disciplinary sanctions for Civil Servants who commit violationsKeywords : Work Discipline, government regulations (PP No 53/ 2010).